ACCELERATING UI LOADING WITH JETPACK COMPOSE: A PERFORMANCE IMPROVEMENT GUIDE - Shanu Sahadevan Mary (INTERNATIONAL JOURNAL OF RESEARCH IN COMPUTER APPLICATIONS AND INFORMATION TECHNOLOGY (IJRCAIT), 2024)
This article provides a practical guide to improving performance in Android applications using Jetpack Compose. It addresses key challenges developers face when building smooth, responsive user interfaces across various device categories. The article explores essential optimization strategies including efficient list rendering through lazy layouts, animation performance tuning, state management techniques, and comprehensive testing approaches. Drawing from real-world implementations and research findings, the article presents proven methods for reducing memory usage, improving frame rates, and enhancing user experience. The article covers both basic optimizations and advanced techniques, offering developers concrete strategies to build high-performance applications that work well across different Android devices.